Defasador de RF ultra faixa larga baseado em tecnologia fot?nica - Cunha, Matheus S?da Borsato (2018)
This work is regarding the development of two photonic-based ultra-broadband radiofrequency (RF) phase shifters for microwaves and millimeter-wave frequency ranges. Initially, the photonics technique responsible for the phase shifting in the optical domain, capable of providing a continuous and tunable phase shift in the electrical domain in an ultra-wideband frequency range. The development methodology of the RF phase shifters is based on four main steps: conception; analytical investigation; numerical simulations; experimental validation and performance analysis in a laboratory environment. The numerical simulations were carried out using the piece of software OptiSystem, whereas the experiments were carried out at the Laboratory WOCA (Wireless and Optical Convergent Access). Numerical results demonstrate the efficiency of the proposed photonic-based RF phase shifter from 10 to 100 GHz with flat phase and amplitude. The initial experimental results validate the proposed photonic-based RF phase shifter operation from 5.0 to 43.5 GHz.